THE STATE OF THE SIRS AND ENDOTHELIAL FUNCTION IN HYPERTENSIVE PATIENTS, STAGE II IN THE PROCESS OF ISCHEMIC HEART DISEASE DEVELOPING - I. M. Fushtey; V. A. Mochonyi; E. V. Sid’; N. F. Efimenko (Zaporožskij Medicinskij Žurnal)
Aim and Methods. Clinical and pathogenetic significance of immuno-inflammatory response in the occurrence of coronary heart disease (CHD) in patients with essential hypertension (EH) is insufficiently studied. In order to determine the concentration of immuno-inflammatory markers in the blood plasma, interleukin-1β (IL-1β), interleukin-10 (IL-10), high-sensitivity C-reactive protein (HS-CRP) and their relationship with endothelial function (according to end-point metabolites of nitric oxide and reactive hyperemia) a comprehensive study of 180 patients with stage II EH was conducted. Clinical examination, determination of serum levels of IL-1β, IL-10, HS-CRP level NO2 and NO3, endothelium-dependent vasodilation were provided.